Standards-based metadata procedures for retrieving data for display or mining utilizing persistent (data-DOI) identifiers - Harvey, Matthew J (J Cheminform, 2015)
BACKGROUND: We describe three different procedures based on metadata standards for enabling automated retrieval of scientific data from digital repositories utilising the persistent identifier of the dataset with optional specification of the attributes of the data document such as filename or media type. RESULTS: The procedures are demonstrated using the JSmol molecular visualizer as a component of a web page and Avogadro as a stand-alone modelling program. We compare our methods for automated retrieval of data from a standards-compliant data repository with those currently in operation for a selection of existing molecular databases and repositories. CONCLUSIONS: Our methods illustrate the importance of adopting a standards-based approach of using metadata declarations to increase access to and discoverability of repository-based data. [Figure: see text]